PERBANDINGAN PENGETAHUAN, SIKAP DAN TINDAKAN MURID TENTANG PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SEKOLAH DASAR YANG MEMILIKI DAN YANG TIDAK MEMILIKI USAHA KESEHATAN SEKOLAH (UKS) DI KECAMATAN MEDAN BARU TAHUN 2013 - Adri Deslita Situmorang; taufik ashar; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2014)
School Health Unit was a health improvement program located in schools with the aim of increasing Clean and Healthy Life Behaviour students. Without a Clean and Healthy Life Behaviour students more easily exposed to diseases such as diarrhea and worm infestation. It can reduce student ability to receive their lessons.This study aims to determine there was difference or not in students knowledge, attitudes and practice about Clean and Healthy Life Behaviour in the school who had and hasn’t had School Health Unit.Research site was in Medan. Population in this study were class III-V in a elementary school who had School Health Unit and a elementary school who hasn’t had School Health Unit, the samples were 70 students from each school. The sampling technique used was stratified random sampling. Data was obtained by questionnaires and interviews, analyzed using the T test for normally distributed data and Mann Whitney test for data not normally distributed.The research results showed that basic sanitation score mean were 15, basic sanitation in a school who had School Health Unit was good with score 14 and a  school who hasn’t had School Health Unit was good too with score 16, implementation of School Health Unit in a school who had School Health Unit was good, and there are differences (p ≤ 0.05) in students knowledge(p=0,001), attitudes (p=0,001) and practice (p=0,001)about Clean and Healthy Life Behaviour in a school who had and hasn’t had School Health Unit.Based on the results of the study, concluded that there are differences in students knowledge, attitudes, and actions about Clean and Healthy Life Behaviour in the school who have School Health Unit and a school who hasn’t had School Health Unit. For recommendation in this research it is expected that the school without School Health Unit make cooperation with local goverment clinic to opening School Health Unit.